BREASTFEEDING BARRIERS AND EXPECTATIONS AMONG MOTHERS AFTER CESAREAN SECTION - Dwi Margareta Andini; Dewi Andariya Ningsih (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Breast milk is a nutritionally balanced food for babies. Breast milk is easy to digest, contains easily absorbed nutrients, provides immunity, and helps mothers and children form an emotional bond. The type of delivery influences the success of exclusive breastfeeding. Moms who have had a caesarean segment run the chance of not only breastfeeding their babies since they are awkward. The mother's pain limits the interaction between mother and baby and makes the mother reluctant to breastfeed her child. This study aimed to look into the breastfeeding experiences of primiparous mothers who had previously had a Caesarean section. This study employed a generic exploratory qualitative research design. Twelve primiparous women with a history of caesarean section served as research informants in this study. They were chosen using a technique known as purposive sampling. A semi-structured interview was used to collect data in the Umbulharjo I Health Center working area in Yogyakarta City from March to June 2023. Creswell, J.W. approach to thematic analysis was used to analyze research data. The analysis yielded two themes: breastfeeding obstacles and breastfeeding mothers' expectations. Improving breastfeeding health promotion and self-efficacy for post-caesarean mothers is expected to broaden the scope of breastfeeding for post-caesarean mothers.